Kajian Penerapan Life Cycle Persfective dengan Penerapan Reduce, Reuse, dan Recycle (3R) di Industri Berbahan Baku Logam dan Plastik Cikarang - Nida Mariam (President University, 2022)
Abstract. Human needs are increasing day by day. To meet these needs, one of the things that should be done are produce these materials or needs, this is related to the manufacturing industry. One of these manufacture is the metal and plastic industry. The manufacturing industry is growing rapidly and is diverse, causing a large environmental effect or influence, if environmental management or control is not carried out. Objectives: One of the efforts that need to be done to protect the environment is conduct a Life Cycle Perfective (LCP) analysis related to the implementation of 3R (Reduce, Reuse, and Recycle). In this study, analyzing the Life Cycle Perspective through the application of the 3R in each production activity or production support. Method and results:This research is done by literature study, observation, and analizing this situation Conclusion: The benefits of this 3R application are felt by the industry, in addition to making production activities more effective and efficient, increasing customer trust, and becoming a culture in environmental protection and environmental prevention activities in the company as well as the actions of every employee. In the future, it will be improved and re-evaluated in accordance with existing production activities and continuous industrial enhancement.